Pengembangan Aplikasi Pendeteksi Kematangan Buah Melon: Studi Kasus Aplikasi Melonku - Ihsanul Fikri Abiyyu; Hilmy Abidzar Tawakal (Jurnal Informatika Terpadu, 2021)
There was research in Sekolah Tinggi Teknologi Terpadu Nurul Fikri about how to check the maturity of melon with the skin of melon. That research used image processing to build an algorithm to find the maturity of melon based on melon skin. The algorithm has been created into programming code and only runs in a command prompt that only some people can use. In order algorithm to can be used by many people, this research will continue the previous research to make a mobile application that connects into an algorithm with a web service. The development methodology that is used in this research is the Rational Unified Process. The mobile development using react-native to make a front end and flask to make a backend. The results of this research are expected to help the community to check the maturity of melons more easily.